(untitled) (Global Journal of Human-Social Science, 2013)
The aim of this research is to un-mask or to explore the facts which are hermetical in the Quaid’s Speech of 11 August, 1947. CDA does not have a specific direction of research. There are many directions of such type of research. It does not have a proper theoretical frame work. There are several approaches to discourse including critical discourse analysis; conversational analysis and similarly many other forms of analysis. This Research is based upon the Van Dajik’s socio cognitive model (2002)." Van Dijk: "in our opinion CDA should deal primarily with the discourse dimensions of power abuse and the injustice and inequality that result from it."